TaRac6 Is a Potential Susceptibility Factor by Regulating the ROS Burst Negatively in the Wheat–Puccinia striiformis f. sp. tritici Interaction - Zhang, Qiong; Zhang, Xinmei; Zhuang, Rui; Wei, Zetong; Shu, Weixue; Wang, Xiaojie; Kang, Zhensheng (Frontiers in Plant Science, 2020)
Rac/Rop proteins play important roles in the regulation of cell growth and plant defense responses. However, the function of Rac/Rop proteins in wheat remains largely unknown. In this study, a small G protein gene, designated as TaRac6, was characterized from wheat (Triticum aestivum) response to Puccinia striiformis f. sp. tritici (Pst) and found to be highly homologous to the Rac proteins identified in other plant species. Transient expression analyses of the TaRac6-GFP fusion protein in Nicotiana benthamiana leaves showed that TaRac6 was localized in the whole cell. Furthermore, transient expression of TaRac6 inhibited Bax-triggered plant cell death (PCD) in N. benthamiana. Transcript accumulation of TaRac6 was increased at 24 hours post-inoculation (hpi) in the compatible interaction between wheat and Pst, whereas it was not induced in an incompatible interaction. More importantly, silencing of TaRac6 by virus induced gene silencing (VIGS) enhanced the resistance of wheat (Suwon 11) to Pst (CYR31) with producing fewer uredinia. Histological observations revealed that the hypha growth of Pst was markedly inhibited along with more H2O2 generated in the TaRac6-silenced leaves in response to Pst. Moreover, transcript levels of TaCAT were down-regulated significantly, while those of TaSOD and TaNOX were up-regulated significantly. These results suggest that TaRac6 functions as a potential susceptibility factor, which negatively regulate the reactive oxygen species (ROS) burst in the wheat–Pst interaction.